1993
DOI: 10.1007/bf00296659
|View full text |Cite
|
Sign up to set email alerts
|

Detection of collagenase mRNA in odontoclasts of bovine root-resorbing tissue by In situ hybridization

Abstract: The odontoclast, which is morphologically similar to osteoclast, is thought to play a major role in root resorption of deciduous teeth. High collagenolytic activity has been detected in the root resorbing tissue. In order to identify collagenase-producing cells and the role of collagenase in root resorption of deciduous tooth, in situ hybridization of collagenase mRNA in bovine root-resorbing tissue sections was performed using a digoxigenin-labeled, nonradioactive RNA probe. Collagenase mRNA expression was cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 16 publications
0
29
0
2
Order By: Relevance
“…Osteoblasts may synthesize procollagenase which becomes trapped in the mineralized matrix for subsequent activation by the OC [30]. In TRAP positive odontoclasts, which resemble OC and resorb dentin, collagenase mRNA has been localized by in situ hybridization [31]. The mechanism of action of TETs on collagenase may relate to binding of the compound to Zn z + at the enzyme's active site.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts may synthesize procollagenase which becomes trapped in the mineralized matrix for subsequent activation by the OC [30]. In TRAP positive odontoclasts, which resemble OC and resorb dentin, collagenase mRNA has been localized by in situ hybridization [31]. The mechanism of action of TETs on collagenase may relate to binding of the compound to Zn z + at the enzyme's active site.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Sasaki and Ueno-Matsuda (1992) have demonstrated that odontoclasts secrete cathepsin B and G into the resorption lacunae of dentine. Although collagenase has been described as being mainly synthesized by osteoblasts but not by osteoclasts (S. Sakamoto and Sakamoto 1982, Okamura et al (1993) have detected the expression of collagenase by in situ hybridization in odontoclasts but not in cementoblasts or the surrounding periodontal fibroblastic cells. In contrast to osteoclasts broadly observable in bone, odontoclasts are temporary and spatially restricted to the formation and localization on root dentine of deciduous teeth, thereby enabling adequate root resorption of the deciduous teeth.…”
Section: Introductionmentioning
confidence: 97%
“…The major source of collagenase in bone is osteoblasts (Vaes et al, 19921, although immunoreactive collagenase in osteoclasts has not been reported , suggesting that collagenase found in resorption lacunae may be secreted by osteoclasts. Further support for this view is provided by the detection of collagenase mRNA by in situ hybridization in odontoclasts (Okamura et al, 1993). The role of collagenase in resorption pits provides an intriguing problem since collagenase is inactive at a low pH.…”
Section: Detection Of Specific Binding Of Calciotrophicmentioning
confidence: 97%